Expanding roles of superoxide dismutases in cell regulation and cancer - Che, Meixia; Wang, Ren; Li, Xiaoxing; Wang, Hui-Yun; Zheng, X.F. Steven (Drug discovery today, 2016)
•Superoxide dismutases (SODs) have important regulatory functions in metabolism, signalling and transcription.•SODs are crucial for cancer cell growth, proliferation, survival and metastasis.•SODs are potential therapeutic targets for drug and radiation therapy for human cancer. Reactive oxygen species (ROS) have important roles in normal physiology and diseases, particularly cancer. Under normal physiological conditions, they participate in redox reactions and serve as second messengers for regulatory functions. Owing to aberrant metabolism, cancer cells accumulate excessive ROS, thus requiring a robustly active antioxidant system to prevent cellular damage. Superoxide dismutases (SODs) are enzymes that catalyze the removal of superoxide free radicals. There are three distinct members of this metalloenzyme family in mammals: SOD1 (Cu/ZnSOD), SOD2 (MnSOD) and SOD3 (ecSOD). SODs are increasingly recognized for their regulatory functions in growth, metabolism and oxidative stress responses, which are also crucial for cancer development and survival. Growing evidence shows that SODs are also potentially useful anticancer drug targets. This review will focus on recent research of SODs in cellular regulation, with emphasis on their roles in cancer biology and therapy.